The Preliminary Development of an in vitro Poultry Cecal Culture Model to Evaluate the Effects of Original XPCTM for the Reduction of Campylobacter jejuni and Its Potential Effects on the Microbiota - Feye, Kristina M.; Rubinelli, Peter M.; Chaney, William Evan; Pavlidis, Hilary O.; Kogut, Michael H.; Ricke, Steven C. (Frontiers in Microbiology, 2020)
Poultry is a major reservoir for the pathogen Campylobacter jejuni. C. jejuni inhabits the poultry gastrointestinal tract as a part of the gut microbiota. The objective of this study was to evaluate both the survival of C. jejuni and the changes in the population dynamics of the cecal microbiome during an in vitro C. jejuni inoculation in the presence or absence of the functional metabolites of Diamond V Original XPCTM (XPC). Two independent trials were conducted. Broiler chickens (n=6 per Trial 1 and n=3 per Trial 2) were raised according to standard industry guidelines and euthanized on Day 41. The ceca were collected aseptically, their contents removed independently and then used in an in vitro microaerobic model with 0.1% cecal contents + Campylobacter with or without 1% XPC (w/v). Before the inoculation with a chloramphenicol resistant marker strain of C. jejuni, the cecal contents were pre-incubated with XPC at 42 °C for 24 h, in a shaking incubator (200 rpm) under microaerobic conditions, then experimentally inoculated with 108/ml of C. jejuni into the appropriate treatment groups. At 0 and 24 h for Trial 1, and 48 h for Trial 2, sub-samples of the culture (n=3 ceca, 2 technical replicates per ceca, XPC alone or ceca culture alone) were enumerated using a Petroff-Hausser counter, and the DNA was extracted for microbiome analysis. DNA was isolated using the Qiagen QIAamp Fast Stool DNA Mini Kit and sequenced using the Illumina MiSeq platform. The reads were filtered, normalized, and assigned taxonomical identities using the QIIME2 pipeline. The relative microbiota populations were identified via ANCOM. Altogether, evidence suggests that XPC alters the microbiome, and in turn reduces Campylobacter survival.